1998
DOI: 10.21273/hortsci.33.3.485a
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Liverwort Growth in Containers Using Irrigation, Mulches, Fertilizers, and Herbicides

Abstract: Liverwort (Marchantia sp.) is often a serious weed in many nursery and greenhouse operations. Combinations of irrigation frequencies, surface mulches, surface fertilizers and herbicides were applied to the surface of the growing medium in 10-cm square pots planted with Rhododendron or Picea. Liverwort infestations were evaluated as the percentage of media surface covered. Mulches were placed at least 1/2-inch thick on the surface of the growing media. Five blocks of two pots per treatment were used in a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…They (Svenson et al, 1997) described pre-emergence control with oxyfluorfen, oryzalin, isoxaben, and oxadiazon as fair, fair to good, fair to good, and fair to very good respectively. Svenson (1998) later documented slightly better preemergence liverwort control with oxadiazon compared with oryzalin in both low-and high-frequency irrigation settings. Wilson and Hughes (1985) reported that oryzalin applied at 9-week intervals provided 99% liverwort control compared with 76% control with oxadiazon applied at a similar frequency.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…They (Svenson et al, 1997) described pre-emergence control with oxyfluorfen, oryzalin, isoxaben, and oxadiazon as fair, fair to good, fair to good, and fair to very good respectively. Svenson (1998) later documented slightly better preemergence liverwort control with oxadiazon compared with oryzalin in both low-and high-frequency irrigation settings. Wilson and Hughes (1985) reported that oryzalin applied at 9-week intervals provided 99% liverwort control compared with 76% control with oxadiazon applied at a similar frequency.…”
mentioning
confidence: 95%
“…It is a primitive spore-bearing plant in the class Hepaticae. Liverwort thrives in conditions with high light (O'Hanlon, 1926), low ultraviolet radiation (True et al, 2006), high humidity or soil moisture (Svenson, 1998), and high fertility. These conditions are typical of many propagation and container production environments.…”
mentioning
confidence: 99%
“…However, these options have met with limited success (File et al 1999;Llewellyn et al 2003;Svenson 1997Svenson , 1998. At this writing, there is no herbicide specifically registered for POST liverwort control.…”
mentioning
confidence: 99%
“…Top dry weights were greater for trees grown with disks or preemergence herbicide, but root dry weights were not different (Table 2). Irrigation or fertilization rates other than those used in this study might alter these results (Svenson, 1998).…”
Section: Resultsmentioning
confidence: 87%
“…Under postal regulations, this paper therefore must be hereby marked advertisement solely to indicate this fact. (Svenson, 1998). They also suppressed weed growth equal to or better than granular or sprayed preemergence herbicides (products not listed) when used on the substrate surface of containergrown azaleas (Rhododendron sp.)…”
Section: Discussionmentioning
confidence: 99%